Prescription characteristics of Xue-Fu-Zhu-Yu-Tang in pain management: a population-based study using the National Health Insurance Research Database in Taiwan - Kuo, Chun-En; Hsu, Sheng-Feng; Chen, Ching-Chih; Wu, Szu-Ying; Hung, Yu-Chiang; Hsu, Chung Y.; Tsai, I.-Ju; Hu, Wen-Long (Frontiers in Pharmacology, 2023)
Objective: To explore the prevalence and distinctive features of Xue-Fu-Zhu-Yu-Tang (XFZYT) prescriptions by analyzing the National Health Insurance Research Database (NHIRD) to identify the specific medical problems under which XFZYT is prescribed. Methods: This nationwide, population-based, cross-sectional study, 109073 XFZYT users and 532848 XFZYT non-users among Chinese herbal product (CHP) users in the NHIRD. Chi-square tests were used to analyze disparities between the XFZYT and non-XFZYT cohorts, and the mean age was evaluated using the Wilcoxon rank-sum test. Logistic regression was used to compute the odds ratios (ORs) and 95% confidence intervals (95% CIs). Results: XFZYT was frequently used to treat pain. The top five conditions that Taiwanese TCM practitioners would prescribe XFZYT were chest pain, headache, myalgia, myositis, lumbago, neuralgia, neuritis, and radiculitis. Conclusions: This study represents an inaugural comprehensive survey conducted on the utilization of XFZYT prescriptions among patients with diverse diseases. XFZYT is mostly used to treat pain conditions in Taiwan. Combined with combination use of other CHPs, XFZYT is used to treat symptoms of the chest and respiratory system, soft tissue conditions, menstruation disorders, and joint and back discomfort. These results suggest that further clinical trials are warranted to verify the effects of XFZYT in pain management.